A nonproteinogenic amino acid, β-tyrosine, accumulates in young rice leaves via long-distance phloem transport from mature leaves. Issue 4 (12th February 2022) - Sakamoto, Shunta; Yoshikawa, Takanori; Teraishi, Masayoshi; Yoshinaga, Naoko; Ochiai, Kumiko; Kobayashi, Masaru; Schmelz, Eric A; Okumoto, Yutaka; Mori, Naoki
ABSTRACT: Oryza sativa L. ssp. japonica cv. Nipponbare produces a nonproteinogenic amino acid (3 R )-β-tyrosine from l -tyrosine by tyrosine aminomutase (OsTAM1). However, physiological and ecological function(s) of β-tyrosine have remained obscure. Often an improved understanding of metabolite localization and transport can aid in design of experiments to test physiological functions. In the current study, we investigated the distribution pattern of β-tyrosine in rice seedlings and found that β-tyrosine is most abundant in the youngest leaves. Based upon observations of high TAM1 activity in mature leaves, we hypothesized that β-tyrosine is transported from mature leaves to young leaves. Patterns of predominant mature synthesis and young leaf accumulation were supported by stable isotope studies using labeled β-tyrosine and the removal of mature leaves. Stem exudate analyses was also consistent with β-tyrosine transport through phloem. Thus, we identify young leaves as a key target in efforts to understand the biological function(s) of β-tyrosine in rice. Graphical Abstract: